A case report of bioprosthetic valve dysfunction after tricuspid valve replacement in a preschool patient: the contribution of pannus and calcification - T. V. Glushkova; E. A. Ovcharenko; A. V. Batranin; K. Yu. Klyshnikov; Yu. A. Kudryavtseva; L. S. Barbarash (Вестник трансплантологии и искусственных органов, 2018)
Aim. To assess the contribution of pannus and calcification to the development of bioprosthetic valve dysfunction after tricuspid valve replacement in a pediatric patient.Materials and methods. A 3-month-old patient presented with tricuspid valve  dysplasia and grade 4 tricuspid insufficiency underwent tricuspid valve  replacement with the bioprosthesis «PeriCor» (ZAO «NeoKor», Russian  Federation). The patient at the age of 6 years required a redo tricuspid valve  replacement 5 years 8 months after initial surgery. Degenerative changes of the  dysfunctional bioprosthetic valve explanted from the tricuspid position were  assessed using macroscopic description and light microscopy. Cellular  composition, the presence of bacteria, colocalization of calcifications with  recipient cells were analyzed. The distribution of calcifications and their volume  in the biomaterial tissue were estimated using microcomputer tomography imaging (micro-CT).Results. Bioprosthetic valve dysfunction was mainly caused by the pannus  formation which was shown to encapsulate the anterior leaflet, resulting in its  total failure and severe stenosis (reduced effective orifice area). There were no  signs of ruptures and perforations in the valve tissues found. All leaflets were  shown to contain predominantly fibroblastic cells and single blood cells, mainly located in the surface layers of the leaflets in the regions without any  signs of calcification. Bacteria staining was negative for all types of the studied biomaterials. Calcifications were present in all xeno-tissue elements of the  explanted bioprosthesis (i.e. leaflets, aortic segment, and pericardium). In  addition, calcifications were also found in pannus growing during a functioning  bioprosthetic valve. Calcifications were predominantly located in the co-optation  and commissure zones of the leaflets. Importantly, massive calcifications were  observed around the bioprosthetic stent frame. The total volume of calcification  accounted for 1/3 of the biological component of the bioprosthesis (729 mm3).Conclusion. According to the data obtained in this study, we may conclude that the primary cause of the bioprosthesis failure was the growth of connective  tissues, resulting in pannus-related dysfunction, rather than severe calcification  of all bioprosthetic components. One may assume that bioprosthetic dysfunction  is related to the peculiarity of the inflammatory response of the preschool  patient. However, this typeof dysfunctions requires further investigation.